Efficiency and effectiveness of social spending - Herrmann, Paul; Tausch, Arno; Heshmati, Almas; Bajalan, Chemen S.J. (Bonn, 2008)
"In this qualitative sociological and quantitative economic policy paper, we start out from the assumption of a very recent European Commission Background paper on the “Efficiency and effectiveness of social spending”, which says the effectiveness of social spending can be defined by the degree to which the realized allocation approaches the socially desired outcome. The conclusions listed in the Commission paper are found far reaching and not supported by the empirical data. We perform such an analysis, starting from advances in recent literature. A more encompassing sociological perspective on the issue and factor analytical calculations is presented, which supports our general argument about the efficiency of the Scandinavian model. The social quality approach provides an alternative perspective on welfare system analysis, focusing on public policies rather than social policies. The empirical evidence, suggests that in terms of the efficiency of the European social model, the geography of comparative performance include: the direct action against social exclusion, health and family social expenditures, the neo-liberal approach, and the unemployment benefit centred approach. Applying rigorous comparative social science methodology, we also arrive at the conclusion that in terms of the initial ECOFIN definition of efficiency, the data presented in this article suggest that apart from Finland and the Netherlands, three new EU-27 member countries, especially the Czech Republic and Slovenia, provide interesting answers to the question about the efficiency of state expenditures in reducing poverty rates."